COVID-19 AND INTELLECTUAL PROPERTY LAW: COMPULSORY LICENSING AND THE ACCESS TO COVID-19 TREATMENT (De Legibus - Law Journal, 2021)
This essay concerns the problematic of the access to Covid-19 treatment at an international scale and the role of Intellectual Property Law. As in past outbreaks, one of the most raised questions is the possibility of patent holder’s rights being an obstacle to the access to treatment. Since the beginning of this pandemic, Compulsory Licensing has been presented as the mechanism capable to guaranteeing Covid-19 treatment globally and rapidly. We propose to analyse this figure and its possible alternatives - Voluntary Licensing, Patent Pools and the Proposal to waive TRIPS Intellectual Property provision. We will then assess which is the most effective solution to overcome this humanitarian crisis without compromising the balance between the right to health and intellectual property rights.